Latilactobacillus sakei Furu2019 and stachyose as probiotics, prebiotics, and synbiotics alleviate constipation in mice - Guo, Yanan; Song, Liqiong; Huang, Yuanming; Li, Xianping; Xiao, Yuchun; Wang, Zhihuan; Ren, Zhihong (Frontiers in Nutrition, 2023)
Introduction Slow transit constipation (STC) is a common disorder in the digestive system. This study aimed to evaluate the effects of stachyose (ST) and Latilactobacillus sakei Furu 2019 (L. sakei) alone or combined on diphenoxylate-induced constipation and explore the underlying mechanisms using a mouse model. Methods ICR mice were randomly divided into five groups. The normal and constipation model groups were intragastrically administrated with PBS. The ST, L. sakei, and synbiotic groups were intragastrically administrated with ST (1.5 g/kg body weight), alive L. sakei (3 × 109 CFU/mouse), or ST + L. sakei (1.5 g/kg plus 3 × 109 CFU/mouse), respectively. After 21 days of intervention, all mice except the normal mice were intragastrically administrated with diphenoxylate (10 mg/kg body weight). Defecation indexes, constipation-related intestinal factors, serum neurotransmitters, hormone levels, short-chain fatty acids (SCFAs), and intestinal microbiota were measured. Results Our results showed that three interventions with ST, L. sakei, and synbiotic combination (ST + L. sakei) all alleviated constipation, and synbiotic intervention was superior to ST or L. sakei alone in some defecation indicators. The RT-PCR and immunohistochemical experiment showed that all three interventions relieved constipation by affecting aquaporins (AQP4 and AQP8), interstitial cells of Cajal (SCF and c-Kit), glial cell-derived neurotrophic factor (GDNF), and Nitric Oxide Synthase (NOS). The three interventions exhibited a different ability to increase the serum excitatory neurotransmitters and hormones (5-hydroxytryptamine, substance P, motilin), and reduce the serum inhibitory neurotransmitters (vasoactive intestinal peptide, endothelin). The result of 16S rDNA sequencing of feces showed that synbiotic intervention significantly increased the relative abundance of beneficial bacteria such as Akkermansia, and regulated the gut microbes of STC mice. In conclusion, oral administration of ST or L. sakei alone or combined are all effective to relieve constipation and the symbiotic use may have a promising preventive effect on STC.